Estimation of confidence intervals for quantiles in a finite population - Chadyšas, Viktoras (Mathematical Modelling and Analysis, 2008)
Confidence intervals provide a way of reporting an estimate of a population quantile along with some information about the precision of estimates. Some procedures that may be used to obtain estimates of confidence intervals for quantiles in a finite population (most of which are based on resampling) are compared in the paper. A simulation study, based on two different artificial populations, is performed and comparisons of the estimation methods proposed for confidence intervals of population quantiles are made.First Published Online: 14 Oct 2010